سياسات الاستثمار في الجزائر بين القطاع الحكومي و القطاع الخاص وأثرها على النمو الاقتصادي - (2021- - دراسة قياسية للفترة ( 199: Investment policies in Algeria between the public and private sectors and their impact on economic growth - Standard study for the period (1990-2021). - عبابو الطيب, (Journal of North African Economies, 2025)
Investment occupies an important place in achieving economic growth, and in Algeria there is a co-integration relationship between government investment spending and private investment with the passage of time despite the uneven increase in the period (1990-2019) when the dominance was for government investment, and this explains that the impact of investment government spending On economic growth is greater than the impact of private investment, and their legacy is positive, but long-term up to 10 years. Nevertheless, there is a possibility of integration between government investment spending and private investment in the short term, and thus the possibility of this integration contributing to accelerating economic growth, especially after reviewing the correlational differences between the two variables Accurately correcting the directions of each sector and drawing a transparent and clear relationship between the two variables by drawing an accurate drawing of the role of each of the two sectors and their effectiveness in the investment policy as a whole Especially after the emergence of signs of a serious investment policy for the period after 2021.